PENDIDIKAN MORAL PESERTA DIDIK MELALUI IMPLEMENTASI TATA TERTIB SEKOLAH DASAR NEGERI INPRES BUMI BAHARI KECAMATAN PALU BARAT - Retolia; Sitti Nadirah (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2018)
An Efforts to improve the morality of learners are always conducted in education. Educational institutions are morally obligated to increase personality development of their students. SDN Inpres Bumi Bahari Kec. Palu Barat through the implementation of school rules, intends to form the character of learners. This circumstance is the basis of this research. This research based on descriptive qualitative methods. The Source of data obtained from principals, teachers, and Learners. This research used varieties methods such as observation, interviews, and documentations in data collecting process. Furthermore, data that has been netted, analyzed using data reduction techniques, data display, and data verification. The results of the study concluded that the application of school rules can shape the behavior of learners to be a good personality. The behavior of learners is directed towards moral learner. The process of character building of learners finds some barriers because learners have a different understanding of school rules order. In addition, many students have a strong influence of the habits they bring from their homes, so they are not familiar with the rules set by their school.